Pengaruh Citra Destinasi dan Komunikasi Pemasaran Terhadap Loyalitas melalui Kepuasan Pengunjung Destinasi Pantai Lon Malang - Nurul Amalia; Pribanus Wantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of destination image and marketing communication on loyalty through visitor satisfaction. This type of research is quantitative research with Structural Equation Modeling data analysis techniques using the SmartPLS version 4.0 statistical program. In this study, the population is not known for certain (infinite) and the sample used is tourists visiting Lon Beach, Malang. This study uses a questionnaire with a Likert Scale. The results of the study obtained that destination image affects loyalty with a p-value <0.05 and t-statistic> 1.96, while destination image does not affect satisfaction with a p-value> 0.05 and t-statistic <1.96, but marketing communication has an effect on loyalty with a p-value <0.05 and t-statistic> 1.96, and communication also has an effect on satisfaction with a p-value <0.05 and t-statistic> 1.96.